Phase equilibria of Bi-Te-RE (Yb,Nd,Sm,Er,Tb) ternary systems at 673K - Zhang L.-G.; Song Q.; Tan M.-Y.; Jiang Y.; Liu L.-B. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The phase equilibria of Bi-Te-RE (Yb, Nd, Sm, Er, Tb) at 673 K were established through equilibrated alloys. The isothermal sections of Bi-Te-RE (Yb, Nd, Sm, Er, Tb) at 673 K were established according to the result of Scanning Electron Microscopy (SEM), Electron probe micro-analysis (EPMA), and Powder X-ray diffractometry (XRD). In the Bi-Te-Yb system at 673 K, the existence of 4 three-phase equilibria (YbTe+Bi2Te3+Te, YbTe+Bi2Te3+β, YbTe+Bi+β, YbTe+Yb5Bi3+Yb4Bi3) was established, while 3 three-phase regions (NdTe2+β+Bi2Te3, NdTe2+β+Bi, Nd2Te3+Bi+BiTeNd) in Bi-Te-Nd system, 3 threephase regions (SmTe3+Te+Bi2Te3, SmTe1.8+Bi2Te3+β, SmTe1.8+β+Bi) in Bi-Te-Nd system, 3 three-phase regions (TbTe3+Te+Bi2Te3, Tb4Te7+Bi2Te3+β, TbTe+Bi+β) in Bi-Te-Nd system, and 4 three-phase regions (ErTe3+Te+Bi2Te3, ErTe3+Bi2Te3+Er2Te3, Bi2Te3+Er2Te3+β, Er2Te3+β+ErTe, β+ErTe+Bi) in Bi-Te-Nd system were also identified, respectively. Among the Bi-Te-RE (Nd, Sm, Er, Tb, Yb) systems, the solubilities of RE in Bi2Te3 were 0.19 at % Nd, 0.22 at % Sm, 0.28 at % Tb, 0.35 at %Er, and 0.37 at % Yb. In general, the maximum solubility of elements in Bi2Te3 phase alloy became larger with the increase in RE atomic number. A ternary compound BiTeNd in the Bi-Te-Nd ternary system was confirmed in this work.